A Brief Analysis of the Application of MyBatis in Java Development - Jiang, Chao; Bao, Zhengde; Li, Chenxi (Journal of Theory and Practice in Engineering and Technology, 2024)
MyBatis is a high-performance JavaEE persistence framework, so in large-scale JavaEE development, developers usually choose it as the persistence framework for their development projects; This article introduces the basic application and working principle of MyBatis in the development of project persistence layer through the case of automatic reply robot. This case uses the MyBatis framework to achieve two basic functions: automatic reply to page messages and information maintenance of backend pages; Through the project case in this article, readers can understand that MyBatis, as a persistence framework, has many benefits: basic ORM implementation, unified management of SQL statements, and implementation of dynamic SQL statements.